2022
DOI: 10.3390/cancers14071623
|View full text |Cite
|
Sign up to set email alerts
|

High Keratin-7 Expression in Benign Peri-Tumoral Prostatic Glands Is Predictive of Bone Metastasis Onset and Prostate Cancer-Specific Mortality

Abstract: Background: New predictive biomarkers are needed to accurately predict metastasis-free survival (MFS) and cancer-specific survival (CSS) in localized prostate cancer (PC). Keratin-7 (KRT7) overexpression has been associated with poor prognosis in several cancers and is described as a novel prostate progenitor marker in the mouse prostate. Methods: KRT7 expression was evaluated in prostatic cell lines and in human tissue by immunohistochemistry (IHC, on advanced PC, n = 91) and immunofluorescence (IF, on locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…Additionally, only 10% of samples showed positive expression of Ck-7 (21,22). Interestingly, the results of the study of Dariane et al showed that Ck-7 is expressed in normal prostate tissue and benign glands around the tumor, mainly in the cells of the basal and suprabasal layers, but it is not present in the luminal cells of the tumor (23). Therefore, the expression of Ck-7 decreases during the development of PAC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only 10% of samples showed positive expression of Ck-7 (21,22). Interestingly, the results of the study of Dariane et al showed that Ck-7 is expressed in normal prostate tissue and benign glands around the tumor, mainly in the cells of the basal and suprabasal layers, but it is not present in the luminal cells of the tumor (23). Therefore, the expression of Ck-7 decreases during the development of PAC.…”
Section: Discussionmentioning
confidence: 99%